Absorbsi Kadmium (Cd) dan Timbal (Pb) oleh Bandeng (Chanos chanos) pada Tambak Komplangan di Desa Tanjung Rejo Kecamatan Percut Sei Tuan - Daniel Abas Herman Silalahi; Yunasfi Djayus; Nurmatias Nurmatias (AQUACOASTMARINE, 2018)
Aplication of silvofishery cultivation technique in TanjungRejo Village, PercutSei Tuan Sub District still not well managed. This happens because it enters The PaluhMerbau water source directly without water management process first. Remembering The PaluhMerbau is still intersect with Deli Estuary that has been polluted heavy metals then the autors are interested to do this research. This study aims to calculate the amount of heavy metal concentrationabsorbed by milkfishin Tanjung Rejo Village Percut Sei Tuan Subdistrict.This scientific report surveyed within a month in July 2017 and analyzed using an atomic absorption spectrophotometer (AAS).The result of UPT LPPMHP Medan test showed that the concentration of cadmium and lead on milkfish’s liver and milkfish’s gill has been contaminated by heavy metals cadmium and lead but still belowquality standards.Keywords: Heavy metal, cadmium, lead, milkfish and silvofishery.